Methodology to Determine the Maximum Rotational Speed for the Arrangement of Buried Permanent Magnets In High-Speed Rotors of Electrical Machines - Lauerburg, Maximilian; Hameyer, Kay (XXVIII. Symposium Electromagnetic Phenomena in Nonlinear Circuits (EPNC 2024): Conference Proceedings, 2025)
A methodology to determine the maximum technically feasible rotational speed of rotors constructed with buried permanent magnets is presented. The maximum achievable rotational speed is reached as soon as the permissible space within the rotor is no longer sufficient for the arrangement of the permanent magnets. The methodology couples mechanical and electromagnetic constraints. The results are evaluated based on a V-arrangement of a buried rotor permanent magnet system.